REDESIGNING ENGLISH SYLLABUS OF THE FOURTH GRADE BASED ON STRENGTHS, WEAKNESSES, OPPORTUNITIES AND THREATS (SWOT) ANALYSIS - German, Emilius (Faculty of Languages Ã¢â¬â¹Ã¢â¬â¹and Arts, State University of Semarang, 2013)
The objectives of the present study are to (1) evaluate the current English syllabus of the fourth grade of elementary school by employing the (SWOT) analysis; 2) redesign current English syllabus based on such analysis; 3) evaluate the effectiveness of the proposed syllabus. The present study applied research and development design which is proposed by Borg and Gall (1983:775). The model was simplified into six stages: Information collecting- this was done by using the SWOT analysis and the strategy of taking the advantages of the opportunities to overcome the weaknesses was adopted to redesign the syllabus, Developing preliminary form of product, Experts and lecturers validation, Product revision, Field testing, Producing final product. The proposed syllabus was tried out at the forth grade of St. Joseph Elementary Schools. It has been tested in try out session. The result shows the significant achievement. Thus, teaching English by using the proposed syllabus for elementary schools students can significantly improve their achievement.